2016
DOI: 10.1002/2211-5463.12133
|View full text |Cite
|
Sign up to set email alerts
|

Mouse‐specific up‐regulation of Ccnb1 expression by miR‐199a‐5p in keratinocyte

Abstract: MicroRNA (miRNA) are a class of single‐stranded, small non‐coding RNA that regulate various biological processes, including skin and hair cycle regulation, by modulating the expression of specific genes at the post‐transcriptional level. Recently, several studies reported that miRNA directly or indirectly up‐regulate target genes. Previously, we performed microarray analysis to identify the target genes of miR‐199a‐5p in a mouse skin keratinocyte cell line and detected more than 200 genes whose expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[9][10][11] Moreover, high expression of CCNB1 and CCNB2 can promote the proliferation and cell cycle progression of keratinocytes, further exacerbating psoriasis manifestations. 12,13 Bioinformatics analyses by Choudhary and Melero showed that CCNB1 is a core target in the onset mechanism of psoriasis and may contribute to the transformation of mild to severe psoriasis. 14,15 Furthermore, Li et al showed that CCNB2 expression ameliorates the symptoms of psoriasis patients.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Moreover, high expression of CCNB1 and CCNB2 can promote the proliferation and cell cycle progression of keratinocytes, further exacerbating psoriasis manifestations. 12,13 Bioinformatics analyses by Choudhary and Melero showed that CCNB1 is a core target in the onset mechanism of psoriasis and may contribute to the transformation of mild to severe psoriasis. 14,15 Furthermore, Li et al showed that CCNB2 expression ameliorates the symptoms of psoriasis patients.…”
Section: Introductionmentioning
confidence: 99%
“…For our purpose, BIRC5 has been shown to be associated with the occurrence of GBM. G2/mitotic-specific cyclin-B1 (CCNB1) is a key factor in initiating mitosis ( 26 ), which plays a certain regulatory role in G2/M transition ( 27 , 28 ). It performs this by acting as the regulatory subunit of the maturity promoter factor (MPF) and interacting with cyclin-dependent kinase (CDK1).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al have shown that Ccnb1 is a target of miR-199a-5p in mouse keratinocytes. 33 Others have validated that Ccnb1 is target of miRNA-410 as its overexpression reduces Ccnb1 protein levels and decreases cell proliferation of gonadotroph tumours. 34 Khan et al reported that miR-379 regulates cyclin B1 expression and is decreased in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent studies have shown that in addition to the ubiquitination and anaphase-promoting complex mentioned above, there are other factors that participate in cyclin B1 regulation. 31,32 Several studies have shown that miR-199a-5p, 33 miR-410 34 and miR-379 35 mediate the cell cycle by directly regulating cyclin B1 (Ccnb1) expression in several cell types of cells. 27,28 Gene expression is repressed by miRNAs through base-pairing with complementary sequences within mRNA molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation